2004
DOI: 10.1103/physrevlett.92.026602
|View full text |Cite
|
Sign up to set email alerts
|

Current-Induced Transverse Spin-Wave Instability in a Thin Nanomagnet

Abstract: We show that an unpolarized electric current incident perpendicular to the plane of a thin ferromagnet can excite a spin-wave instability transverse to the current direction if source and drain contacts are not symmetric. The instability, which is driven by the current-induced "spin-transfer torque", exists for one current direction only.PACS numbers: 75.75.+a, 75.40.Gb, Ferromagnets serve as spin filters for an electrical current passing through the magnet: the spin of the electrons that are transmitted throu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
145
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(154 citation statements)
references
References 26 publications
6
145
2
1
Order By: Relevance
“…Özyilmaz et al [36] experimentally observed current-induced excitation of a single ferromagnetic layer. For an asymmetric Cu/Co/Cu nanopillar structure, current-induced excitations were observed for only one polarity of the current, where, according to the prediction [27], the lateral spin transfer torque should increase the magnetization inhomogeneity. In addition, they did not observe such excitations in a symmetric structure, as expected from the discussion above.…”
Section: Previous Studies On Non-local Spin Transfer Torque Due To Lamentioning
confidence: 99%
See 4 more Smart Citations
“…Özyilmaz et al [36] experimentally observed current-induced excitation of a single ferromagnetic layer. For an asymmetric Cu/Co/Cu nanopillar structure, current-induced excitations were observed for only one polarity of the current, where, according to the prediction [27], the lateral spin transfer torque should increase the magnetization inhomogeneity. In addition, they did not observe such excitations in a symmetric structure, as expected from the discussion above.…”
Section: Previous Studies On Non-local Spin Transfer Torque Due To Lamentioning
confidence: 99%
“…Spin transfer torques caused by lateral spin diffusion, which we will refer to as "lateral spin transfer torque", were proposed by Polianski and Brouwer [27]. The geometry of the system under consideration is shown in Fig.…”
Section: Basic Concept Of Non-local Spin Transfer Torque Due To Latermentioning
confidence: 99%
See 3 more Smart Citations